2017
DOI: 10.1097/sla.0000000000002371
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients With Cystic Lesions of the Pancreas Undergo Long-term Radiographic Surveillance?

Abstract: Cyst size stability at the 5-year time point did not preclude future growth, cross-over to resection, or carcinoma development. Patients who were stable at 5 years had a nearly 3-fold higher risk of developing cancer compared with the general population and should continue long-term surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 16 publications
2
37
0
1
Order By: Relevance
“…An issue of much debate is whether the risk of malignancy increases over time. Some recent studies have shown that even small SB‐IPMN may evolve into malignancy after 5 or 10 years, and that a stable cyst size for 5 years does not preclude future growth . Because our study population has a mean follow‐up of 50 months, we are not yet able to determine these long‐term risks.…”
Section: Discussionmentioning
confidence: 97%
“…An issue of much debate is whether the risk of malignancy increases over time. Some recent studies have shown that even small SB‐IPMN may evolve into malignancy after 5 or 10 years, and that a stable cyst size for 5 years does not preclude future growth . Because our study population has a mean follow‐up of 50 months, we are not yet able to determine these long‐term risks.…”
Section: Discussionmentioning
confidence: 97%
“…They found a low 5-year risk of PC (2%) for patients without HRS or WF according to the IAP guidelines, whereas the risk increased progressively in the case of WF (4.1%) or HRS (49.7%), suggesting a tailored approach for surveillance strategies. The study from the Memorial Sloan Kettering Cancer Center presents data extracted from one of the largest databases but focuses on a small group of patients affected by PCN with more than 5 years of follow-up [21]. These PCN change over time in 44% of cases, presenting an overall rate of progression towards PC of 1%.…”
Section: New Perspectives From Observational Studiesmentioning
confidence: 99%
“…As a matter of fact, after the AGA guidelines first proposed surveillance discontinuation after 5 years, several studies have attempted to identify a subpopulation of PCN in which follow-up could be potentially safely discontinued [18,20,21]. However, it has not yet been demonstrated that a prolonged follow-up could reduce PC-related mortality thanks to early diagnosis or prevention.…”
Section: New Perspectives From Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent article published by the ACR Incidental Findings Committee, as the first revision of the document released in 2010, Megibow et al (15) stated that the recommendations are based not only on the level of evidence but also on personal experience, when evidence is lacking, and their consensus is a guidance rather than formal guidelines. The main changes proposed in the management of patients with incidental pancreatic cysts were a longer follow-up period (10 years)-due to reports of the development of invasive pancreatic adenocarcinoma after 5 years of follow-up (16,17) -a more liberal use of EUS-FNA, and the recommendation to discontinue follow-up beyond 80 years of age, except when there are symptoms. It should be keep in mind that only cysts with a diameter > 1.5 cm contain a sufficient volume of fluid (1-2 mL) to allow reliable cytological and biochemical analyses (18) .…”
mentioning
confidence: 99%